MAPPING JUNIOR HIGH SCHOOL STUDENTS’ FUNCTIONAL LITERACY COMPETENCE - Burhan Nurgiyantoro; Beniati Lestyarini; Dwi Hanti Rahayu (Jurnal Cakrawala Pendidikan, 2020)
Literacy issues have probably been a special concern of many countries. In Indonesia, there have also been several surveys regarding the literacy of school students. This study aims to map the functional literacy of junior high school (JHS) students by focusing on various types of literacy and how each of them contributes to the overall functional literacy. This is quantitative survey research whose subjects were JHS students in four regencies and one municipality of the Special Region of Yogyakarta, with a total sample member of 246 students. The research instrument was an extension of the National Assessment for Adult Literacy (NAAL) with some additions of functional literacy types suggested in the FGD. Data were collected by using a test and analyzed through descriptive statistics and confirmatory factor analysis using the structural equation model with the Lisrel program. The results reveal that the functional literacy of the JHS students is mostly in the “medium” (83.3%), “low” (15.4%), and “high” (1.2%) category. Of the 15 types of literacy, two of them (13.33%), namely prose and cultural literacy make “high” contribution to the functional literacy as a whole, and two others (document and environmental literacy) also support to a “medium” extent (13.33%), while the rest (60%) are categorized as having “low” contribution. This likely implies the importance of fostering various types of functional literacy at school for students to have the ability to develop their personal and social functions.